Strategic Advancements for Competitive Edge in the Food Industry: Kemajuan Strategis untuk Keunggulan Kompetitif di Industri Makanan - Ravshanovich, Xamraev Nodirbek (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the strategic management and enhancement of competitiveness within the food industry. Amidst a backdrop of fluctuating market conditions and a need for modernization, this research identifies a significant gap in the effective utilization of foreign investments and the adaptation of industry practices to contemporary standards. The primary aim of this research is to propose methodologies for fostering investment, modernizing operations, and expanding production capacities to stabilize and grow the market presence of food industry enterprises. Employing a methodological approach that combines theoretical frameworks with empirical data analysis, the findings suggest that increased competition and new production capabilities can significantly improve market supply and price stability. The implications of this research underscore the necessity for strategic interventions that not only respond to current industry demands but also anticipate future market conditions, thereby ensuring sustainable development and competitive advantage in the food industry. Highlights: Foreign Investment: Essential for technology infusion and practice improvement. Operational Modernization: Adapts enterprises to contemporary market demands. Production Expansion: Increases supply and stabilizes prices through new capacities. Keywords: Food Industry, Management Strategy, Market Stability, Production Expansion, Competitive Mechanism